Ten‐day triple therapy versus sequential therapy versus concomitant therapy as first‐line treatment for Helicobacter pylori infection. Issue 7 (July 2015) - Ang, Tiing Leong; Fock, Kwong Ming; Song, Mingjun; Ang, Daphne; Kwek, Andrew Boon Eu; Ong, Jeannie; Tan, Jessica; Teo, Eng Kiong; Dhamodaran, Subbiah
Abstract Background and Aim Clarithromycin‐based triple therapy (TT) is the first‐line treatment for Helicobacter pylori infection in Singapore. There is awareness that TT may no longer be effective due to increased clarithromycin resistance rates. Sequential therapy (ST) and concomitant therapy (CT) are alternative treatment regimens. This study aimed to compare the efficacy of 10‐day TT, ST, and CT as first‐line treatment for H. pylori infection. Methods A randomized study conducted in a teaching hospital. Patients aged 21 years and older with newly diagnosed H. pylori infection were randomized to 10‐day TT, ST, or CT. Treatment outcome was assessed by 13‐carbon urea breath test at least 4 weeks after therapy. Intention to treat (ITT), modified ITT (MITT), and per protocol (PP) analyses of the eradication rates were performed. Results A total of 462 patients were enrolled (ST: 154; TT 155; CT 153). Patient demographics were similar. Eradication rates for ST versus TT versus CT: ITT analysis: 84.4% versus 83.2% versus 81.7% (P = not significant [NS]); MITT analysis: 90.3% versus 92.1% versus 94.7% (P = NS); PP analysis: 94.1% versus 92.8% versus 95.4% (P = NS). Antibiotic resistance rates for amoxicillin, clarithromycin, and metronidazole were 4.7%, 17.9%, and 48.1%, respectively. Dual clarithromycin and metronidazole resistance occurred in 7.5%. Dual resistance and lack of compliance were predictors of treatment failure. Conclusions TT, ST, and CT all achieved eradication rates above 80% on ITT and above 90% on MITT and PP analyses. Dual resistance and lack of compliance were predictors of treatment failure (clinicaltrials.gov: NCT02092506).